Chemistry, structure and function of approved oligonucleotide therapeutics. Issue 6 (7th March 2023) - Egli, Martin; Manoharan, Muthiah
Abstract: Eighteen nucleic acid therapeutics have been approved for treatment of various diseases in the last 25 years. Their modes of action include antisense oligonucleotides (ASOs), splice-switching oligonucleotides (SSOs), RNA interference (RNAi) and an RNA aptamer against a protein. Among the diseases targeted by this new class of drugs are homozygous familial hypercholesterolemia, spinal muscular atrophy, Duchenne muscular dystrophy, hereditary transthyretin-mediated amyloidosis, familial chylomicronemia syndrome, acute hepatic porphyria, and primary hyperoxaluria. Chemical modification of DNA and RNA was central to making drugs out of oligonucleotides. Oligonucleotide therapeutics brought to market thus far contain just a handful of first- and second-generation modifications, among them 2′-fluoro-RNA, 2′- O -methyl RNA and the phosphorothioates that were introduced over 50 years ago. Two other privileged chemistries are 2′- O -(2-methoxyethyl)-RNA (MOE) and the phosphorodiamidate morpholinos (PMO). Given their importance in imparting oligonucleotides with high target affinity, metabolic stability and favorable pharmacokinetic and -dynamic properties, this article provides a review of these chemistries and their use in nucleic acid therapeutics. Breakthroughs in lipid formulation and GalNAc conjugation of modified oligonucleotides have paved the way to efficient delivery and robust, long-lasting silencing of genes. This review provides an account of the state-of-the-art of targeted oligo delivery to hepatocytes.